Peran Yayasan CIQAL (Center for Improving Qualified Activity in Life of People with Disabilities) sebagai Policy Entrepreneur dalam Menyusun Agenda Kebijakan Penyandang Disabilitas di Daerah Istimewa Yogyakarta - Isni Wahidiyah Susanto (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2022)
The existence of persons with disabilities in society is one of the important things to be considered by the state, or in this case the government, because persons with disabilities are part of the community who also have the same position, rights, obligations and roles. According to Law Number 8 of 2016 Article 1 paragraph 1, people with disabilities are defined as any person with physical, intellectual, mental, and/or sensory limitations in the long term who in interacting with the environment can experience obstacles. and difficulties to participate fully and effectively with other citizens on the basis of equal rights. However, the need for special treatment given to persons with disabilities is usually misunderstood by the general public which ultimately leads to acts of discrimination against groups of people with disabilities. Seeing the inequality in policies regarding people with disabilities in DI Yogyakarta, the CIQAL Foundation (Center for Improving Qualified Activity in Life of People with Disabilities) pays attention to fighting for the rights of people with disabilities by encouraging changes to laws and regulations in DI Yogyakarta. This research is a qualitative research with a literature study that uses books and other literatures as the main object (Hadi, 1995). The results of this study were two programs provided by the CIQAL Foundation for persons with disabilities in DI Yogyakarta, namely advocacy and empowerment programs.